Between Ethos and Moralité: Reading La Fontaine's "Préface" to the Fables - Bold, Stephen (Dalhousie French Studies)

(untitled) (Department of French, Dalhousie University, 2021)
This paper proposes a reading of La Fontaine’s puzzling and coy preface to his first volume of Fables. Presented at the start as a friendly debate between the author and a rival, the “Préface” becomes an ironic sort of performance art that reveals the fabulist’s own ambivalence toward a genre that has come to him cloaked in the sober robes of a moralizing pedagogy. La Fontaine tries on the costume and does his best to play the part, composing his role from the illustrious examples of Socrates — a fabulist in extremis — and eventually a crafty Aesop, only to show us little by little that he is more a poet and artist than a moralist. Distrustful of those who would lecture on virtue and rectitude, La Fontaine’s teaching anticipates at once Rousseau’s negative education in the Émile and also Victor Turner’s pedagogy of anti-structure.